Mutual fund quality, its importance and the most decisive characteristics - The perspective of Finnish mutual funds’ managers - Maunula, Kati (My University, 2022)
Investing in mutual funds has become increasingly popular globally and in Finland. As more people invest in mutual funds, funds’ quality is becoming a central issue. The purpose of this Master’s thesis is to study how important quality is for mutual funds. Also, the decisive charac-teristics of mutual fund quality are examined. Finnish funds’ managers’ perspective is exam-ined in the thesis. Their perspective is central, as they have an in-depth understanding of funds and a direct impact on them. This study focuses on studying conventional mutual funds. A mu-tual fund is an investment product that combines investors’ assets and acquires various invest-ments in its portfolio. The decisive characteristics affecting the quality of the funds were sought in the past litera-ture. The literature focuses on studying the impact of different fund attributes on perfor-mance. Performance is one of the eight quality dimensions according to David Garvin’s (1984) quality theory. The theory was chosen to be applied because it has been widely used as a theo-retical framework for the analysis of the quality of intangible and tangible products. A mutual fund can be classified as an intangible product because it is an instrument designed to meet customers’ needs. The found characteristics’ importance was asked to be assessed in an email survey. Based on the results, it was possible to rank the characteristics using a quantitative Fuzzy TOPSIS method. The most decisive factors are in order of importance: risk-adjusted profit, fund man-ager skill, fund age, turnover rate, fund manager reputation, responsibility and sustainability, fund size and management fee. The survey also provided background information on the im-portance of the factors. Additionally, respondents mentioned other important attributes, but their statistical significance was low. The results of this thesis can be used to develop higher quality mutual funds. Higher quality products benefit both investors and fund management companies, for example, by improving customer satisfaction and increasing sales. In addition, the results of the thesis can be used to compare funds and in the marketing of funds. This Master’s thesis offers a new research perspective regarding the relationship between quality and mutual funds. The relationship has not been profoundly studied earlier and based on the responses to the survey, fund managers consider quality as an important aspect. Therefore, there is an interest and a need for more research on the topic.

Sijoitusrahastoihin sijoittamisesta on tullut sekä Suomessa, että maailmalla yhä suositumpaa viime vuosien aikana. Kun sijoitusrahastoihin sijoitetaan yhä enemmän, on rahastojen laadusta tullut keskeisempi aihe. Tämän Pro gradu- työn tarkoituksena onkin tutkia kuinka tärkeää laatu on sijoitusrahastolle. Lisäksi tutkitaan sijoitusrahastojen laatuun eniten vaikuttavia tekijöitä. Edellä mainittuja asioita tutkitaan suomalaisten rahastojen hoitajien näkökulmasta. Heidän näkökulmansa on keskeinen, sillä heillä on syvällinen ymmärrys rahastojen luonteesta ja suora vaikutus niihin. Tässä tutkimuksessa keskityttiin käsittelemään tavallisia sijoitusrahastoja poislukien erikoissijoitusrahastot. Sijoitusrahasto tarkoittaa sijoitustuotetta, joka kerää yksittäisten sijoittajien varoja yhteen ja hankkii varoilla erilaisia sijoituksia portfolioonsa. Rahastojen laatuun vaikuttavia keskeisimpiä ominaisuuksia etsittiin aiheeseen liittyvästä kirjallisuudesta. Aiempi kirjallisyys keskittyy tutkimaan eri rahaston ominaisuuksien vaikutusta suorituskykyyn. Suorituskyky on yksi kahdeksasta laadun ulottuvuudesta David Garvinin (1984) laatuteorian mukaan. Teoria valikoitui käytettäväksi, koska sitä on laajasti käytetty aineettomien ja aineellisten hyödykkeiden laadun analysoinnin teoreettisena kehyksenä. Sijoitusrahasto voidaankin luokitella aineettomaksi hyödykkeeksi, koska se on aineeton väline jonka tarkoituksena on täyttää jokin asiakkaan tarve. Kirjallisuudesta löydettyjen ominaisuuksien tärkeyttä pyydettiin arvioimaan sähköpostikyselyssä. Tulosten perusteella pystyttiin asettamaan ominaisuudet tärkeysjärjestykseen käyttäen kvantitatiivista Fuzzy TOPSIS-metodia. Ominaisuudet ovat tärkeysjärjestyksessä riskikorjattu tuotto, rahastonhoitajan ammattitaito, rahaston ikä, kiertonopeus, rahastonhoitajan maine, vastuullisuus, rahaston koko ja hallinnointipalkkio. Kyselyn avulla saatiin myös perusteluja ominaisuuksien tärkeydelle. Lisäksi vastaajat mainitsivat muita tärkeitä ominaisuuksia, mutta niiden tilastollinen merkittävyys jäi pieneksi. Tämän tutkielman tuloksia voidaan käyttää sijoitusrahastojen kehittämisessä laadukkaammiksi. Laadukkaammat tuotteet hyödyttävät sekä sijoittajia, että rahoitusyhtiöitä esimerkiksi parantamalla asiakastyytyväisyyttä ja lisäämällä myyntiä. Lisäksi tutkielman tuloksia voidaan käyttää vertailtaessa eri rahastoja sekä rahastojen markkinoinnissa. Tämä pro gradu-tutkielma tarjoaa uuden tutkimusnäkökulman liittyen laadun ja sijoitusrahastojen suhteeseen. Suhdetta ei ole aiemmin tutkittu kattavasti ja kyselyssä saatujen vastausten perusteella rahastonhoitajat pitävätkin laatua tärkeänä rahastoille. Aiheeseen liittyvälle tutkimukselle onkin siis kiinnostusta ja tarvetta.
Keywords: mutual funds; quality; investment products; investments; investment funds; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management